Reproductive Assurance Maintains Red-Flowered Plants of Lysimachia arvensis in Mediterranean Populations Despite Inbreeding Depression - Jiménez-López, Francisco J. (Front Plant Sci, 2020)
Flower color polymorphism, an infrequent but phylogenetically widespread condition in plants, is captivating because it can only be maintained under a few selective regimes but also because it can drive intra-morph assortative mating and promote speciation. Lysimachia arvensis is a polymorphic species with red or blue flowered morphs. In polymorphic populations, which are mostly Mediterranean, pollinators prefer blue-flowered plants to the red ones, and abiotic factors also favors blue-flowered plants. We hypothesize that the red morph is maintained in Mediterranean areas due to its selfing capacity. We assessed inbreeding depression in both color morphs in two Mediterranean populations and genetic diversity was studied via SSR microsatellites in 20 natural populations. Results showed that only 44–47% of selfed progeny of the red plants reached reproduction while about 72–91% of blue morph progeny did it. Between-morph genetic differentiation was high and the red morph had a lower genetic diversity and a higher inbreeding coefficient, mainly in the Mediterranean. Results suggest that selfing maintaining the red morph in Mediterranean areas despite its inbreeding depression. In addition, genetic differentiation between morphs suggests a low gene flow between them, suggesting reproductive isolation.